Respuesta :
At first, weIf assumed that the two expressions are equal and then we can write the following and solve for x
5(3x-6)=15x-30
Then perform transposition method such as shown below
15x-30=15x-30
15x-15x=-30+30
0=0
They are equal since the derived values on both sides is the same which is zero.
5(3x-6)=15x-30
Then perform transposition method such as shown below
15x-30=15x-30
15x-15x=-30+30
0=0
They are equal since the derived values on both sides is the same which is zero.
Answer:
Te answer is (A) They are equivalent if the value for 5(3x + 6) is greater.
Step-by-step explanation:
I got it right on edge
Hope it helps!